2016
DOI: 10.4012/dmj.2015-162
|View full text |Cite
|
Sign up to set email alerts
|

Time-related surface modification of denture base acrylic resin treated by atmospheric pressure cold plasma

Abstract: The changes of denture base acrylic resin surface properties under cold plasma and the relationships with time were investigated. Cold plasma treated the specimens for 30 s, 60 s, 90 s, and 120 s, respectively. Water contact angles were measured immediately after the treatment, 48 h, 15 days and 30 days later. Surface roughness was measured with 3-D laser scanning microscope. Candida albicans adherence was evaluated by CFU counting. Chemical composition was monitored by X-ray photoelectron spectroscopy analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Specimen dimensions were verified using a digital caliper (Mitutoyo Corp.). Likewise, specimens were stored in distilled water for 48 hours to minimize residual monomers …”
Section: Methodsmentioning
confidence: 99%
“…Specimen dimensions were verified using a digital caliper (Mitutoyo Corp.). Likewise, specimens were stored in distilled water for 48 hours to minimize residual monomers …”
Section: Methodsmentioning
confidence: 99%
“…Another aspect to enhance the effect of CAP I and II might have been an extended irradiation time, as it has been found that prolonged plasma treatment of 8–10 min destroys E. faecalis biofilms completely . Some investigations showed no significant changes with prolonged application times and the risk of tissue damage should be considered . Another issue discussed in wound healing to enhance the effects is a repeated and/or combined application of CAP .…”
Section: Discussionmentioning
confidence: 99%
“…609.003.1) jet and the round metal electrodes volume DBD plasma (INP Greifswald, Germany) are effective in against a wide range of pathogens including Candida albicans [147, 148]. It was reported that the argon/oxygen single‐electrode plasma jet seemed to be a promising and convenient strategy for preventing the early adherence of C. albicans on the acrylic resins, which would be greatly benefit for the potential dental applications [149]. As drug therapy is usually limited to the time in which signs of infection are present, the tissue‐tolerable plasma jet is an effective treatment tool for the denture stomatitis patients.…”
Section: State‐of‐the‐art Of Plasma Stomatologymentioning
confidence: 99%